Length-Weight Relationship of 60 Fish Species From the Eastern Mediterranean Sea, Egypt (GFCM-GSA 26) - Mehanna, Sahar F.; Farouk, Alam Eldeen (Frontiers in Marine Science, 2021)
Length-weight relationships (LWRs) are described for 60 important pelagic and demersal fish species caught during fishing surveys using trawl fishing gear in the Eastern Mediterranean, Egypt (General Fisheries Commission for the Mediterranean GFCM-GSA 26), and the data collected from the commercial catch during the period from July 2017 to December 2018. Linear regression using natural logarithmic transformation data was performed to calculate the a and b coefficients of LWR for 60 fish populations covering 23 families, 43 genera, and 60 species inhabiting GSA 26. The samples size, minimum and maximum lengths and weights with their mean and SD, LWR constants, ± 95% confidence interval (CI) of b, r2, and the type of growth were calculated and summarized. This study reports the first LWR estimates for 35 species in the Egyptian waters of the Mediterranean Sea.